Current time-to-positivity of blood cultures in febrile neutropenia: a tool to be used in stewardship de-escalation strategies. (April 2019) - Puerta-Alcalde, P.; Cardozo, C.; Suárez-Lledó, M.; Rodríguez-Núñez, O.; Morata, L.; Fehér, C.; Marco, F.; Del Río, A.; Martínez, J.A.; Mensa, J.; Rovira, M.; Esteve, J.; et al.
Abstract: Objectives: We aimed to describe the current time-to-positivity (TTP) of blood cultures in individuals with onco-haematological diseases with febrile neutropenia. We assessed the probability of having a multidrug-resistant Gram-negative bacilli (MDR-GNB) bloodstream infection (BSI) 24 h after cultures were taken, to use this information for antibiotic de-escalation strategies. Methods: BSI episodes were prospectively collected (2003–2017). When a patient experienced more than one BSI, only one episode was randomly chosen. Time elapsed from the beginning of incubation to a positive reading was observed; TTP was recorded when the first bottle had a positive result. Results: Of the 850 patient-unique episodes, 323 (38%) occurred in acute leukaemia, 185 (21.8%) in non-Hodgkin's lymphoma and 144 (16.9%) in solid neoplasms. Coagulase-negative staphylococci (225; 26.5%), Escherichia coli (207; 26.1%), Pseudomonas aeruginosa (136; 16%), Enterococcus spp. (81; 9.5%) and Klebsiella pneumoniae (67; 7.9%), were the most frequent microorganisms isolated. MDR-GNB were documented in 126 (14.8%) episodes. Median TTP was 12 h (interquartile range 9–16.5 h). Within the first 24 h, 92.1% of blood cultures were positive (783/850). No MDR-GNB was positive over 24 h. Of the 67 (7.9%) episodes with a TTP ≥24 h, 25 (37.3%) occurred in patients who were already receiving active antibiotics against the isolated pathogen. Most common isolations with TTP ≥24 h were coagulase-negative staphylococci, candidaemia and a group of anaerobic GNB. Conclusions: Currently, the vast majority of BSI in individuals with onco-haematological diseases with febrile neutropenia have a TTP <24 h, including all episodes caused by MDR-GNB. Our results support reassessing empiric antibiotic treatment in neutropenic patients at 24 h, to apply antibiotic stewardship de-escalation strategies.